Pengaruh Latihan Ball Feeling dan Agillity Terhadap Kemampuan Menggiring Bola Pemain Futsal di SMP Negeri 3 Palembang - Ryvaldo Syaputra; Hetilaniar Hetilaniar; Mutiara Fajar (Jurnal Cakrawala Pendidikan dan Biologi, 2024)
The problem in this study is the ability to dribble the ball in futsal games at SMP Negeri 3 Palembang is not optimal. Some of the causes of the athlete's less than optimal dribbling ability are because in dribbling, players have not been supported by good agility, coaches have never provided agility training methods that lead to these abilities, as seen by the frequent loss of the ball by athletes while being dribbled and easily taken by opponents. The population in this study were 30 extracurricular futsal students at SMP Negeri 3 Palembang. The sample in this study was 30 extracurricular futsal students at SMP Negeri 3 Palembang. The technique for taking samples in this study used Total Sampling. This research method is Experimental research, The design in this study is "two group pretest posttest design" the results of Hypothesis H1 in this study where the results of the t-test are known that the t-count value is 6.770 while T table α 0.05 (15-1) = 14 is 1.761, because the t-count value> t table (6.770> 1.761), this means that there is an influence, namely HA 1: There is an influence of ball feeling training on the ability to dribble the ball in futsal players at SMP Negeri 3 Palembang, the results of the second hypothesis t-test H2 are known that the t-count value is 4.297 while T table α 0.05 (15-1) = 14 is 1.761, because the t-count value> t table (4.297> 1.761), this means that there is an influence, namely HA 2: There is an influence of ball agility training on the ability to dribble the ball in futsal players SMP Negeri 3 Palembang, the results of the third hypothesis t-test H3 that the t-value of the pretest-posttest ball feeling is greater, namely 6,770, than the t-value of the pretest-posttest agility, namely 4,297, then this means that ball feeling training is more effective than agility training in improving dribbling skills